A bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite film and its preparation method and application

The bacterial cellulose/chisoligosaccharide/γ-polyglutamate composite membrane prepared by dynamic and static combination fermentation and in-situ modification methods solves the problem of structure collapse of the bacterial cellulose membrane after drying, and achieves high yield, excellent mechanical properties and good drug sustained release effect.

CN115715771BActive Publication Date: 2025-03-28ANHUI POLYTECHNIC UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211437419.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-15
Publication Date
2025-03-28
Estimated Expiration
2042-11-15

AI Technical Summary

Technical Problem

After drying, the moisture evaporates in the bacterial cellulose membrane, causing the collapse of the internal 3D network structure, resulting in poor mechanical properties and irreversible hydrophilicity.

Method used

Carboxylic activation was used to prepare covalently bound binet interpenetrating bacterial cellulose/chisoligosaccharide/γ-polyglutamate composite membranes with covalently bound bi-network interpenetrating bacterial cellulose/chisoligosaccharide/γ-polyglutamate composite membranes.

Benefits of technology

The yield of bacterial cellulose is improved, and the obtained composite membrane has excellent mechanical properties and swelling properties, and has excellent drug loading and sustained release capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115715771B_ABST
    Figure CN115715771B_ABST
Patent Text Reader

Abstract

The invention discloses a bacterial cellulose / chitosan oligosaccharide / gamma-polyglutamic acid composite membrane and a preparation method and application thereof. The invention uses bacterial cellulose, chitosan oligosaccharide and gamma-polyglutamic acid as main components of the composite membrane, and uses carboxyl activation to prepare a covalently bonded double-network interpenetrating composite membrane based on a dynamic and static combined fermentation and an in-situ modification method. The method not only improves the yield of the bacterial cellulose membrane, but also improves the mechanical and swelling properties of the obtained composite membrane, and simultaneously has excellent drug loading capacity and good drug sustained-release capacity, and has potential for application in the field of drug carriers or sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane materials, and in particular relates to a bacterial cellulose / chitosan oligosaccharide / gamma-polyglutamic acid composite membrane and a preparation method and application thereof. Background Art

[0002] Bacterial cellulose (BC) is an unbranched long-chain polymer connected by β-1,4 glucoside bonds obtained by fermentation of microorganisms such as Acetobacter xylinum. It has the advantages of high purity, degree of polymerization, Young's modulus, water absorption, crystallinity, biocompatibility and good biodegradability. It is widely used in wound dressings, drug sustained-release carriers and other fields.

[0003] However, bacterial cellulose membranes have the problems of high fermentation production costs, low yields and low product added value. Since bacterial cellulose molecules are combined in the form of hydrogen bonds, the evaporation of water after drying will cause the internal 3D network structure to collapse, making the hydrophilicity of BC irreversible, and the structure cannot be restored after swelling with water, resulting in poor mechanical properties and irreversible hydrophilicity. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite membrane and its preparation method and application. The present invention uses bacterial cellulose, chitosan oligosaccharide and γ-polyglutamic acid as the main components of the composite membrane, and uses carboxyl activation to prepare a covalently bound double network interpenetrating composite membrane based on dynamic and static combined fermentation and in-situ modification methods. This method not only improves the yield of bacterial cellulose, but also the obtained composite membrane has excellent mechanical properties and swelling properties, and at the same time has excellent drug loading capacity, and has good sustained release capacity for drugs, and has the potential for application in the field of drug carriers or sensors.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite film, the preparation method comprising the following steps:

[0007] (1) inoculating Acetobacter xylinum seed liquid into a fermentation medium, performing dynamic fermentation for a period of time, and then switching to static fermentation, and then adding a sterile chitosan oligosaccharide solution to continue static fermentation to obtain a bacterial cellulose / chitosan oligosaccharide composite film;

[0008] (2) the bacterial cellulose / chitosan oligosaccharide composite film obtained in step (1) is immersed in an alkaline solution and heated at a constant temperature of 75 to 85° C. for 30 to 45 minutes;

[0009] (3) soaking the bacterial cellulose / chitosan oligosaccharide composite film treated in step (2) in an ethanol solution for 10 to 12 hours, then rinsing to neutrality and drying;

[0010] (4) Soaking the dry film obtained in step (3) in a carboxyl-activated γ-polyglutamic acid solution for 1.5 to 3 hours, and then rinsing and drying to obtain a bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite film.

[0011] In step (1), the dynamic fermentation time of Acetobacter xylinum is 2 to 4 hours, and the static fermentation time is 2 days; after adding the sterile chitosan oligosaccharide solution, the static fermentation time is 6 to 8 days.

[0012] In step (1), the fermentation medium components are: 60-70 g / L glucose, 10-15 g / L yeast extract, 3-5 g / L disodium hydrogen phosphate dodecahydrate, 0.4-0.6 g / L citric acid, and 0.1-0.3 g / L anhydrous magnesium sulfate.

[0013] In step (1), the method for preparing the xylinum Acetobacter seed solution is as follows: inoculating the xylinum Acetobacter slant into a seed culture medium, and culturing at 100-120 rpm for 22-28 hours; the components of the seed culture medium are: 40-60 g / L glucose and 4-6 g / L yeast extract.

[0014] In step (1), the mass concentration of the sterile chitosan oligosaccharide solution is 16.5% to 24.75%; the volume ratio of the sterile chitosan oligosaccharide solution to the fermentation medium is 1:8 to 10.

[0015] In step (2), the alkali solution is a NaOH solution with a concentration of 0.05 to 0.2 mol / L. In step (3), the volume concentration of the ethanol solution is 60% to 80%.

[0016] In step (4), the preparation method of the carboxyl-activated γ-polyglutamic acid solution is: fully dissolving γ-polyglutamic acid in a MES buffer solution with a pH of 5 to 6, then adding EDC and NHS, and stirring the reaction at 20 to 25° C. for 10 to 20 minutes.

[0017] The mass ratio of γ-polyglutamic acid to chitosan oligosaccharide is 1:2-4.

[0018] The present invention also provides a bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite membrane prepared according to the above preparation method, which is a double network skeleton structure formed based on covalent bonding, which can not only increase the bacterial cellulose yield, but also the obtained composite membrane also has excellent mechanical properties and swelling properties.

[0019] The present invention also provides application of the bacterial cellulose / chitooligosaccharide / γ-polyglutamic acid composite membrane as a carrier material.

[0020] In the preparation method of the bacterial cellulose / chitooligosaccharide / γ-polyglutamic acid composite film provided by the present invention, bacterial cellulose, chitooligosaccharide, and γ-polyglutamic acid with excellent biocompatibility, safety, and degradability are used as raw materials. Bacterial cellulose is a long-chain polymer connected by β-1,4 glucosidic bonds obtained by fermentation of microorganisms such as Acetobacter xylinum, and has high purity, degree of polymerization, Young's modulus, water absorption, and crystallinity. Chitooligosaccharide is a natural polycationic compound with multiple physiological functions such as antibacterial and antioxidant properties. Chitooligosaccharide is an ideal polymer combined with bacterial cellulose because it has a similar structure to bacterial cellulose. Chitooligosaccharide is added to the fermentation medium after the dynamic and static combined fermentation is completed. The obtained bacterial cellulose / chitooligosaccharide composite film can not only make the bacterial cellulose have the performance of chitooligosaccharide, but also reduce the rate of conversion of glucose into gluconic acid in the fermentation broth due to the antioxidant property of chitooligosaccharide, thereby increasing the film yield. The structure of γ-polyglutamic acid contains a large number of hydrophilic groups such as carboxyl and hydroxyl groups, and has a strong water-locking ability. The carboxyl groups in the carboxyl-activated γ-polyglutamic acid can combine with the chitosan oligosaccharide in the bacterial cellulose / chitosan oligosaccharide composite membrane through a covalent reaction to form a relatively strong network structure, thereby forming a covalently bonded double-network interpenetrating bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite membrane with the 3D network structure of the bacterial cellulose itself. This composite membrane not only has excellent mechanical properties, but also has excellent swelling properties and good water vapor permeability.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] (1) The present invention proposes for the first time to increase the yield of bacterial cellulose film by combining dynamic-static fermentation with in-situ modification. The yield of dynamic-static fermentation is higher than that of pure static fermentation. In addition, due to the antioxidant properties of chitosan oligosaccharides, the yield of bacterial cellulose is further improved on the basis of in-situ modification and addition of chitosan oligosaccharides.

[0023] (2) The present invention prepares a covalently bonded double-network interpenetrating bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite membrane by combining a carboxyl activation reaction with an in-situ modification. The formation of covalent bonds improves the mechanical properties of the composite membrane, and the double-network interpenetrating structure further enhances the mechanical properties and swelling properties of the composite membrane.

[0024] (3) The composite membrane preparation process of the present invention is simple, has low cost, low equipment requirements, and is green and pollution-free, and has great development potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a surface scanning electron micrograph of the bacterial cellulose / chitosan oligosaccharide composite film in Comparative Example 2;

[0026] Figure 2This is a surface scanning electron micrograph of the bacterial cellulose / chitooligosaccharide composite film of the bacterial cellulose / chitooligosaccharide / γ-polyglutamic acid composite film in Example 1;

[0027] Figure 3 The infrared spectra of the bacterial cellulose / chitooligosaccharide / γ-polyglutamic acid composite film in Example 1, the bacterial cellulose / chitooligosaccharide composite film in Comparative Example 2, and the pure static bacterial cellulose film in Comparative Example 3;

[0028] Figure 4 The yield measurement results of the bacterial cellulose film (a) in Comparative Example 3, the bacterial cellulose / chitosan oligosaccharide composite film (c) in Comparative Example 2, and the dynamic and static fermentation bacterial cellulose film (b) in Comparative Example 1;

[0029] Figure 5 The mechanical properties test results of the bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite film (b) in Example 1, the bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid 1 composite film (c) in Example 2, and the static fermentation bacterial cellulose film (a) in Comparative Example 3;

[0030] Figure 6 The swelling performance test results of the dynamic and static bacterial cellulose film (a) in Comparative Example 1, the bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite film (b) in Example 1, the bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid 1 composite film (c) in Example 2, and the bacterial cellulose / chitosan oligosaccharide composite film (d) in Comparative Example 2;

[0031] Figure 7 The test results of methylene blue loading on the dynamic and static bacterial cellulose membrane (a) in Comparative Example 1, the bacterial cellulose / chitooligosaccharide membrane (b) in Comparative Example 2, and the bacterial cellulose / chitooligosaccharide / γ-polyglutamic acid composite membrane (c) in Example 1;

[0032] Figure 8 The methylene blue loading and release performance tests were performed on the dynamic and static bacterial cellulose membrane (a) in Comparative Example 1, the bacterial cellulose / chitooligosaccharide membrane (b) in Comparative Example 2, and the bacterial cellulose / chitooligosaccharide / γ-polyglutamic acid composite membrane (c) in Example 1;

[0033] Fig. 9 The antibacterial test results of benzalkonium chloride were loaded on the dynamic and static bacterial cellulose membrane (a) in Comparative Example 1, the bacterial cellulose / chitooligosaccharide membrane (b) in Comparative Example 2, the bacterial cellulose / chitooligosaccharide / γ-polyglutamic acid composite membrane (c) in Example 1, the negative control (d) and the positive control (e). DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with the embodiments.

[0035] The raw materials involved in the embodiments are as follows:

[0036] Acetobacter xylinum seed solution: inoculate the Acetobacter xylinum slant into a seed culture medium consisting of 50 g / L glucose and 5 g / L yeast extract, and culture at 120 rpm for 24 h.

[0037] The composition of the fermentation medium is: 70 g / L glucose, 14 g / L yeast extract, 4 g / L disodium hydrogen phosphate dodecahydrate, 0.5 g / L citric acid, 0.2 g / L anhydrous magnesium sulfate, and the solvent is deionized water.

[0038] Example 1

[0039] A method for preparing a bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite film comprises the following steps:

[0040] (1) 3 mL of Acetobacter xylinum seed liquid was inoculated into 50 mL of fermentation medium, and the fermentation was carried out at 220 rpm for 3 h before switching to static fermentation. 5 mL of a sterile chitosan oligosaccharide solution with a mass concentration of 24.75% was added thereto at 2 d of fermentation, and the fermentation was continued for 10 d. The composite film on the surface of the fermentation liquid was then removed and washed with deionized water to obtain a bacterial cellulose / chitosan oligosaccharide composite film;

[0041] (2) immersing the bacterial cellulose / chitosan oligosaccharide composite film obtained in step (1) in a 0.1 mol / L NaOH solution and heating in a water bath at 80° C. for 40 min;

[0042] (3) taking out the membrane immersed in the NaOH solution in step (2), immersing it in a 70% volume concentration ethanol solution for 12 h, and then taking out the membrane and rinsing it with deionized water until it is neutral;

[0043] (4) drying the film obtained in step (3) in a 45° C. forced air drying oven for 12 h until constant weight is reached;

[0044] (5) 3.375 g of γ-polyglutamic acid was dissolved in a MES buffer solution with a pH of 5.5, and after it was fully dissolved, 8 mg of EDC and 22 mg of NHS were added, and the mixture was fully dissolved at 600 rpm for 15 min to obtain a carboxyl-activated γ-polyglutamic acid solution, and the dry film obtained in step (4) was immersed in the above solution for 2 h to obtain a bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite film;

[0045] (6) The bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite membrane in step (5) was rinsed with deionized water to remove the remaining γ-polyglutamic acid and carboxyl activator, and then placed in a 40-50° C. forced air drying oven to dry for 12 h until constant weight was reached.

[0046] Example 2

[0047] A method for preparing a bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid 1 composite film, the other steps are the same as those in Example 1, except that the amount of γ-polyglutamic acid added is 2.25 g.

[0048] Comparative Example 1

[0049] A method for preparing a dynamic and static combined fermentation bacterial cellulose film comprises the following steps:

[0050] (1) Inoculate 3 mL of Acetobacter xylinum seed solution into 50 mL of culture medium, perform dynamic fermentation at 220 rpm for 3 h, then switch to static fermentation and ferment for 10 days to obtain bacterial cellulose film;

[0051] (2) immersing the obtained bacterial cellulose composite film in a 0.1 mol / L NaOH solution and heating it in a water bath at 80°C for 40 min;

[0052] (3) taking out the membrane immersed in the NaOH solution in step (2), immersing it in a 70% volume concentration ethanol solution for 12 h, and then taking out the membrane and rinsing it with deionized water until it is neutral;

[0053] (4) The film obtained in step (3) was placed in a 45°C forced air drying oven and dried for 12 h until constant weight was reached.

[0054] Comparative Example 2

[0055] A method for preparing a bacterial cellulose / chitosan oligosaccharide composite film comprises the following steps:

[0056] (1) 3 mL of Acetobacter xylinum seed solution was inoculated into 50 mL of culture medium, and the culture medium was subjected to dynamic fermentation at 220 rpm for 3 h, and then switched to static fermentation. On the 2nd day of fermentation, 5 mL of sterile chitosan oligosaccharide solution with a mass concentration of 24.75% was added thereto. As the culture medium was switched to static fermentation for 10 days, a bacterial cellulose / chitosan oligosaccharide composite film was obtained;

[0057] (2) soaking the obtained bacterial cellulose / chitosan oligosaccharide composite film in 0.1 mol / L NaOH solution and heating it in a water bath at 80°C for 45 min;

[0058] (3) taking out the membrane immersed in the NaOH solution in step (2), immersing it in a 70% volume concentration ethanol solution for 12 h, and then taking out the membrane and rinsing it with deionized water until it is neutral;

[0059] (4) The washed neutral membrane is placed in a 45°C forced air drying oven and dried for 12 hours until constant weight is reached.

[0060] Comparative Example 3

[0061] A method for preparing a pure static fermentation bacterial cellulose membrane comprises the following steps:

[0062] (1) Inoculating 3 mL of Acetobacter xylinum seed solution into 50 mL of culture medium, and performing static fermentation for 10 days to obtain bacterial cellulose film;

[0063] (2) immersing the obtained bacterial cellulose composite film in a 0.1 mol / L NaOH solution and heating it in a water bath at 80°C for 40 min;

[0064] (3) taking out the membrane immersed in the NaOH solution in step (2), immersing it in a 70% volume concentration ethanol solution for 12 h, and then taking out the membrane and rinsing it with deionized water until it is neutral;

[0065] (4) drying the film obtained in step (3) in a 45° C. forced air drying oven for 12 h until constant weight is reached;

[0066] Test Case

[0067] 1. Electron microscope detection

[0068] The electron microscope was used to observe Example 1 and Comparative Example 3. The results are as follows: Figure 1 , 2 As shown, Figure 1 The bacterial cellulose membrane (BC membrane) in Comparative Example 3 shown in FIG. 1 is a three-dimensional network composed of nanofibers. The irregular layout of the nanofibers makes the bacterial cellulose composite membrane have a low-density, highly porous nanostructure. Compared with the pure bacterial cellulose membrane, Figure 2 The structure of the carboxyl-activated bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid 1 membrane prepared in Example 1 is more compact. The carboxyl-activated γ-polyglutamic acid is covalently bonded to the amino groups of chitosan oligosaccharide and diffused into the pores of the BC membrane, making the fiber surface rougher, the pore size further reduced, and the structure becoming a denser mesh structure.

[0069] 2. Infrared detection

[0070] FT-IR was used to detect Example 1 and Comparative Example 2. Figure 3 As shown, at 3353cm -1 A broad peak appeared at 2923 cm-1, which is related to the stretching vibration of the OH group, the dominant functional group of the bacterial cellulose matrix. The stretching vibration peaks of CH and COC are at 2923 cm-1, -1 and 1063cm -1 1637cm -1 The peak at 1445 cm represents the expansion and contraction of the carbonyl group. The chemical structure of chitosan oligosaccharide is similar to that of bacterial cellulose. The peaks at 1445 cm -1 and 1370cm -1 New characteristic peaks of amide II and amide III bonds appeared. 3277cm -1 and 1581cm-1 The peaks are carboxylic acid and NH stretching after adding γ-polyglutamic acid. Compared with bacterial cellulose, the peak is at 3300-3400cm -1 The composite films shifted to lower wavenumbers, which may be due to the formation of hydrogen bonds.

[0071] 3. Membrane production detection

[0072] The membrane yields obtained from Comparative Examples 1, 2 and 3 were calculated using the weighing method. Figure 4 As shown, the BC film yield obtained by the combination of dynamic and static fermentation in Comparative Example 1 is significantly higher than that of pure static fermentation in Comparative Example 3, proving that the dynamic and static combined fermentation is beneficial to increasing the yield of BC film. Although static fermentation is beneficial to the production of BC film, the low oxygen flux during static fermentation causes slow growth of the bacteria, which in turn leads to low BC film yield. In the dynamic and static combined fermentation in Comparative Example 3, the appropriate rotation speed increases the oxygen flux in the culture medium, providing good conditions for the growth and reproduction of the bacteria, thereby promoting the increase in film yield. In Comparative Example 2, after adding chitosan oligosaccharides to the culture medium after the dynamic fermentation, the bacterial cellulose film yield is further improved on the basis of the dynamic and static combined fermentation. This is because chitosan oligosaccharides have antioxidant properties, which enable them to reduce the rate of oxidation of glucose to gluconic acid after addition, promote the growth of Acetobacter xylinum, and thus increase the bacterial cellulose film yield.

[0073] 4. Mechanical properties testing

[0074] The films obtained in Example 1, Example 2 and Comparative Example 3 were subjected to uniaxial tensile tests using a texture analyzer. The film samples were cut into strips with a length of 40 mm and a width of 10 mm. The measurement range was 5000 cN, the preload force was 10 cN, the clamp distance was 25 mm, and the tensile rate was 5 mm / s. The test results are shown in Table 1. Figure 5 As shown. The mechanical properties of the bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite membrane obtained after carboxyl activation in Examples 1 and 2 are significantly better than those of the pure bacterial cellulose membrane obtained in Comparative Example 3. The carboxyl activators EDC and NHS easily react with the carboxyl groups of γ-polyglutamic acid to generate active NHS ester intermediates, which are finally combined with the amino groups of chitosan oligosaccharides through covalent reactions. Compared with the electrostatic bonding method, it is more solid, so that the breaking stress is increased by about 2 times compared with pure bacterial cellulose. Although the elongation at break has decreased, it is not obvious, and the elastic modulus has also increased compared with pure bacterial cellulose. The occurrence of this phenomenon is also due to the effect of covalent bonds and the formation of a double network structure.

[0075] 5. Swelling performance test

[0076] The films obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were dried to completely remove moisture, and the dried samples were immersed in distilled water and weighed once after 5 minutes, and then weighed every 10 minutes until the re-weighing weight reached a constant (W w : BC weight after swelling; W d : sample dry weight).

[0077]

[0078] The results are as follows Figure 6 As shown, the swelling performance of the bacterial cellulose / chitosan composite film obtained in Comparative Example 2 is greatly reduced compared with the pure bacterial cellulose obtained in Comparative Example 1, because the addition of chitosan oligosaccharides makes the pores of the bacterial cellulose film denser, resulting in a significant decrease in its swelling performance. The swelling performance of the bacterial cellulose / chitosan oligosaccharides / γ-polyglutamic acid obtained after carboxyl activation in Example 1 is comparable to that of the pure bacterial cellulose film; this is because although the composite film is denser and the pores are reduced after carboxyl activation, the carboxyl groups in the γ-polyglutamic acid after carboxyl activation can be combined with the chitosan oligosaccharides in the bacterial cellulose / chitosan oligosaccharide composite film through covalent reaction to form a relatively strong network structure, thereby forming a covalently bonded double network interpenetrating composite film with the 3D network structure of the bacterial cellulose film itself, and the formation of the double network supports the 3D structure of the original structure of the membrane, reducing the collapse of the internal structure caused by the loss of water molecules in the membrane during drying. At the same time, the γ-polyglutamic acid added in the composite membrane of the double network skeleton structure is a biodegradable, edible, and highly biocompatible anionic polymer with excellent hygroscopicity, so it can make up for the reduction in swelling performance that may be caused by the denser structure of the bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite membrane. The swelling performance of the bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid 1 composite membrane obtained in Example 2 is greatly reduced compared with the pure bacterial cellulose obtained in Comparative Example 2 and the bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite membrane obtained in Example 1, indicating that the amount of polyglutamic acid will affect the performance of the composite membrane, especially the effect on the swelling performance is more significant, and the addition of appropriate γ-polyglutamic acid is a key condition for the carboxyl activation reaction. Excessive addition causes an increase in the cost of preparing the composite membrane, and less γ-polyglutamic acid cannot provide sufficient carboxyl groups, which is not conducive to the formation of a double network skeleton structure composite membrane.

[0079] 6. Methylene blue loading and release performance test

[0080] Methylene blue was used as a model drug to evaluate the loading and release functions of the membrane materials obtained in Comparative Example 1, Comparative Example 2 and Example 1.

[0081] Prepare a stock solution of methylene blue model in distilled water with a final concentration of 0.1 mg / mL.2 The composite film was placed in 5 mL of drug model solution, and at the selected loading time point, the model solution was collected in a cuvette and analyzed by UV spectrophotometer.

[0082]

[0083] Where XX is the loaded model drug; A max,d represents the maximum absorbance of the model drug solution before incubation of the membrane sample, while A max , t It represents the maximum absorbance of the solution supernatant after incubation of membrane samples at the selected loading time point.

[0084] Different samples loaded with model drugs were added to 5 mL of pH 7.4 PBS buffer solution, placed in a shaker, and shaken at 70 rpm at 37 ° C. Take out 200 μL of solution at regular intervals and add an equal amount of new buffer. Use a UV spectrophotometer to detect the absorbance at the wavelength corresponding to the drug model, and then calculate the release amount (Cumulative Release, CR) of the drug model according to the following formula.

[0085] CR(mg)=VeΣ n-1 C n-1 +V0C n

[0086] Where V e and V0 are 200 μL and 5 mL respectively. n and C n-1 are the concentrations of the drug model in the solution after n and n-1 samplings, respectively. All tests were repeated three times. Figure 7 As shown, the bacterial cellulose / chitooligosaccharide film in Comparative Example 2 and the bacterial cellulose / chitooligosaccharide / γ-polyglutamic acid film in Example 1 have comparable loading performance for methylene blue, and are significantly higher than the dynamic and static bacterial cellulose film in Comparative Example 1. This is because chitooligosaccharide is negatively charged under neutral conditions and can bind to the positively charged model drug methylene blue through electrostatic action, thus having a higher drug loading capacity. The bacterial cellulose / chitooligosaccharide / γ-polyglutamic acid film obtained after carboxyl activation has a slightly lower drug loading capacity than the bacterial cellulose / chitooligosaccharide film, because the carboxyl-activated chitooligosaccharide part binds to the carboxyl group of γ-polyglutamic acid, resulting in the presentation of the above results. The bacterial cellulose film obtained in the dynamic and static state can only load methylene blue through adsorption due to its single structural component, thus having a lower loading capacity.

[0087] The surface of most chronic bacterial infection wounds is weakly alkaline, so the in vitro release of drugs in a weakly alkaline (pH 7.4) environment is of great significance. Although the loading performance of bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid membrane for methylene blue is slightly lower than that of bacterial cellulose / chitosan oligosaccharide membrane, Figure 8 It can be seen that the bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid film has a higher drug release capacity. The release rates of the three films were all high within the first 5 hours, but after 5 hours, the drug release rate of the dynamic and static bacterial cellulose in Comparative Example 1 decreased significantly. In contrast, the bacterial cellulose / chitosan oligosaccharide in Comparative Example 2 and the bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid film in Example 1 still showed a steady sustained release trend after 5 hours, with a sustained release time of up to 140 hours, and had a high sustained release capacity, which met the requirements of long-term stable drug delivery of wound dressings.

[0088] 7. Benzalkonium chloride loading and antibacterial performance testing

[0089] The antibacterial effect of the membrane materials obtained in Comparative Example 1, Comparative Example 2 and Example 1 after loading with benzalkonium chloride was detected by flow cytometry.

[0090] First, the dynamic and static bacterial cellulose membrane in Comparative Example 1, the bacterial cellulose / chitosan oligosaccharide membrane in Comparative Example 2, and the bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid membrane in Example 1 were soaked in 0.008% benzalkonium chloride solution for 48h for loading of benzalkonium chloride, and then 5mL pH7.4 PBS buffer was used for extraction for 12h, and the supernatant was centrifuged for standby use. Escherichia coli and Staphylococcus aureus were cultured overnight to the logarithmic growth phase, centrifuged at 4000r / min for 10min to collect the bacteria, and the PBS buffer was repeatedly resuspended and rinsed for 2 times. The bacteria were resuspended with 1mL of the extract of different samples, and the bacteria that were not treated by adding 1mL PBS to resuspend were used as negative controls, and the bacteria that were inactivated by adding 1mL PBS and 100°C boiling water bath were used as positive controls, mixed and placed in a shaking table at 37°C and 150r / min for incubation for 45min, then centrifuged at 4000r / min for 10min to collect the bacteria, and 1mL PI dye was added for light-proof staining for 30min. The cells were centrifuged at the same speed for 10 min to collect the bacteria, and the number of dead cells was analyzed by flow cytometry after resuspending in PBS.

[0091] The results are as follows Fig. 9As shown, similar to the sustained-release results, the three membrane materials have good antibacterial effects on Escherichia coli and Staphylococcus aureus. The bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid membrane in Example 1 has the strongest antibacterial effect, which is related to the sustained-release performance of the drug. The antibacterial ability of bacterial cellulose / chitosan oligosaccharide in Comparative Example 2 is second, which is related to the charge of chitosan oligosaccharide. The dynamic and static bacterial cellulose in Comparative Example 1 lacks a strong interaction force with the drug, resulting in explosive release of the drug, and due to limited loading capacity, it exhibits lower antibacterial performance than the other two membranes.

[0092] It can be seen from the above test results that the bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite film provided by the present invention has excellent mechanical properties and swelling properties, and at the same time has excellent drug loading capacity and good drug sustained release ability, and the sustained release time can be as long as 140h.

[0093] The detailed description of a bacterial cellulose / chitooligosaccharide / γ-polyglutamic acid composite film and its preparation method and application with reference to the above-mentioned embodiments is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a bacterial cellulose / chitooligosaccharide / γ-polyglutamic acid composite film, characterized in that: The preparation method comprises the following steps: (1) inoculating Acetobacter xylinum seed liquid into a fermentation medium, and switching to static fermentation after a period of dynamic fermentation, and then adding a sterile chitosan oligosaccharide solution to continue static fermentation to obtain a bacterial cellulose / chitosan oligosaccharide composite film; (2) The bacterial cellulose / chitosan oligosaccharide composite film obtained in step (1) is immersed in an alkaline solution and heated at a constant temperature of 75-85° C. for 30-45 min; (3) Soaking the bacterial cellulose / chitosan oligosaccharide composite film treated in step (2) in an ethanol solution for 10 to 12 hours, then rinsing to neutrality and drying; (4) Soaking the dry film obtained in step (3) in a carboxyl-activated γ-polyglutamic acid solution for 1.5 to 3 hours, rinsing and drying to obtain a bacterial cellulose / chitosan oligosaccharide / γ-polyglutamic acid composite film.

2. The preparation method according to claim 1, characterized in that: In step (1), the dynamic fermentation time of Acetobacter xylinum is 2 to 4 hours, and the static fermentation time is 2 days; after adding the sterile chitosan oligosaccharide solution, the static fermentation time is 6 to 8 days.

3. The preparation method according to claim 1, characterized in that: In step (1), the fermentation medium components are: 60-70 g / L glucose, 10-15 g / L yeast extract, 3-5 g / L disodium hydrogen phosphate dodecahydrate, 0.4-0.6 g / L citric acid, and 0.1-0.3 g / L anhydrous magnesium sulfate.

4. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the sterile chitosan oligosaccharide solution is 16.5% to 24.75%; and the volume ratio of the sterile chitosan oligosaccharide solution to the fermentation medium is 1:8 to 10.

5. The preparation method according to claim 1, characterized in that: In step (2), the alkali solution is a NaOH solution with a concentration of 0.05-0.2 mol / L.

6. The preparation method according to claim 1, characterized in that: In step (3), the volume concentration of the ethanol solution is 60% to 80%.

7. The preparation method according to claim 1, characterized in that: In step (4), the preparation method of the carboxyl-activated γ-polyglutamic acid solution is: fully dissolving γ-polyglutamic acid in a MES buffer solution with a pH of 5-6, then adding EDC and NHS, and stirring the reaction at 20-25° C. for 10-20 min.

8. The preparation method according to claim 1, characterized in that: The mass ratio of γ-polyglutamic acid to chitosan oligosaccharide is 1:2~4.

9. The bacterial cellulose / chitooligosaccharide / γ-polyglutamic acid composite film prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the bacterial cellulose / chitooligosaccharide / γ-polyglutamic acid composite membrane as claimed in claim 9 in the preparation of carrier materials.